THE STATUTORY ARRANGEMENT OF ARTICLE 27 PERPU NO. 1 YEAR 2020 (VIEWED FROM PRESIDENTIAL AUTHORITY, IMMUNITY RIGHTS AND ESTABLISHMENT OF LEGAL REGULATIONS) - Mustakim Mustakim; Tb. M. Ali Asgar; Masidin Masidin (Universitas Nasional, 2020)
The spread of Corona Virus Disease 2019 (Covid-19) in Indonesia is getting wider and results in so many effects. Besides mortality and economy, this country experiences also a lot of problems. To overcome the Covid-19 pandemic, President Joko Widodo had issued various kind of regulations; one of them is the government regulation in lieu of law (Perppu) No. 1 Year 2020 about national financial policy and financial system stability to handle Covid-19 pandemic and/or in order to face the threat that is dangerous for national economy and/or financial system stability. However, a lot of expert and scholars said that Perpu (the government regulation in lieu of law) No. 1 Year 2020 resulted in legal problems. Therefore, the research question of this study is questioning “have the government regulation in lieu of law (Perppu) No. 1 Year 2020 fulfilled the requirement of force majeure condition as what has already been stated in Articel 22 UUD NRI Year 1945? And how is the substance of the regulation of Article 27 point (2) and (3) Perpu No. 1 Year 2020 correlated with immunity rights, and the principles of the establishment of legal regulation in Indonesia? The method used in the study was normative. The approach used was legal regulations and legal principles of the establishment of legal regulations. The result found out that the government regulation in lieu of law Perpu No. 1 Year 2020 published by President Joko Widodo to hold Covid-19 is his right in accordance with the clauses of Article 22 UUD NRI Year 1945, however article 27 point (2) and (3) Perpu No. 1 Year 2020 violate the basic principles of the establishment of legal regulation and it would be potential that the provision of this article lead to uncertainty and injustice.